A Secure System for Buying and Verifying the Authenticity of Drugs Using Blockchain Technology - Ravindran, K.; Pranav Niranjan, J.; Sam Osborn, A. (Asian Journal of Science and Applied Technology, 2023)
In the healthcare sector, ensuring the safety and legitimacy of drugs is a top priority. Counterfeit pharmaceuticals are a major problem for the industry, as they not only cause financial losses but also endanger public health and safety. These fake medications are hazardous or inefficient, putting lives at risk. The dissemination of fake medications has not been stopped by the use of conventional techniques for confirming drug legitimacy. This project presents a novel way to improve the security and authenticity of pharmaceutical purchases by utilizing blockchain technology. The key focus of this innovative project is to devise a blockchain-based secure system that will enable drug producers, distributors, and consumers to safely check the legitimacy of pharmaceuticals and track their provenance throughout the supply chain. The utilization of decentralized and immutable properties of blockchain technology makes it possible to create a transparent and impenetrable platform for documenting and confirming drug-related transactions. The blockchain will securely store every stage of the pharmaceutical supply chain, from production to retail, establishing a transparently traceable framework. Implementing a secure blockchain-based system for drug authentication helps effectively build trust within the pharmaceutical supply chain, protect consumers from counterfeit drugs, and make a positive impact on the overall improvement of public health. The transparency and security offered by blockchain technology in drug transactions have the potential to revolutionize the pharmaceutical industry, fostering a more reliable environment for drug procurement and distribution.